Perlindungan Hukum Bagi Penggugat Atas Kerugian Tindak Pidana Penipuan - I Putu Arya Suarnata Wibawa; I Wayan Novy Purwanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The word law comes from the Arabic al-hukm with literally alhukm meaning a rule. In the trial program the judge can become a law, if there is no regulation in this case, it will be the responsibility of the judge to find the legal regulation. This research aims to find out how the legal protection for the loser is from punishing others, as well as finding out that his inheritance can be a guarantee of legal protection for the injured party for a crime committed by the party in buying protection for formal or material losses. The method used in this research is normative legal writing, the methods used are Case Approach and Statute Approach. The case method is carried out by examining cases related to the problems faced which have become court policies and have permanent legal force. The results of the research show that prosecution needs to be based on strong reasons and evidence if this action is an act that has violated the law, if the reasons and evidence cannot be held accountable so that the lawsuit is based on a prosecution that cannot be carried out by law in court. From this, legal protection is needed for the plaintiff who loses from the criminal action.